VD_FINDINFO Décision / 2012 / 16 vom 12. Oktober 2011 - VD Tribunal cantonal (2011)
NON-LIEU, FRAIS DE LA PROCÉDURE, CONTRAVENTION DE POLICE DE DROIT CANTONAL | 319 CPP (CH), 352 CPP (CH), 393 al. 1 let. a CPP (CH), 426 al. 2 CPP (CH)